The association of bicycle‐related genital numbness and Sexual Health Inventory for Men (SHIM) score: results from a large, multinational, cross‐sectional study - Baradaran, Nima; Awad, Mohannad; Gaither, Thomas W.; Fergus, Kirkpatrick B.; Ndoye, Medina; Cedars, Benjamin E.; Balakrishnan, Ashwin S.; Eisenberg, Michael L.; Sanford, Tom; Breyer, Benjamin N. (BJU international, 2019)
Objective To assess the association of genital numbness and erectile dysfunction in male cyclists. Subjects and methods Cyclists were recruited through Facebook advertisements and outreach to sporting clubs. This is a secondary analysis of a larger epidemiological population‐based study that examined sexual and urinary wellness in athletes. We queried cycling habits and erectile function using Sexual Health Inventory for Men (SHIM). Results A total of 2 774 male cyclists were included in the analysis. Amongst cyclists, there was a statistically significant increase in the trend of genital numbness presence with more years of cycling (P = 0.002), more frequent weekly cycling (P < 0.001), and longer cycling distance at each ride (P < 0.001). Less frequent use of padded shorts (odds ratio [OR] 0.14, P < 0.001) and lower handlebar (OR 0.49, P < 0.001) were associated with numbness, but body mass index (BMI) (OR 1.1, P = 0.33) and age (OR 1.2, P = 0.15) were not. In a multivariate logistic regression model, after adjusting for age, BMI, and lifetime miles (calculated by average daily cycling mileage × cycling days/week × cycling years.), there were no statistically significant differences in mean SHIM score between cyclists with and cyclists without numbness (20.3 vs 20.2, P = 0.83). However, interestingly, the subset of cyclists who reported numbness in the buttock reported statistically significantly worse SHIM scores (20.3 vs 18.4, P < 0.001). This association was not present in cyclists who reported numbness in the scrotum, penis, or perineum and remained significant after adjusting for overall biking intensity. Conclusion Cyclists report genital numbness in proportion with biking intensity but numbness is not associated with worse sexual function in this cohort.